Nano-Publics Communicating Nanotechnology Applications, Risks, and Regulations - Gehrke, Pat J. (Springer International Publishing, 2018)
This book discusses the results and implications of a two-year public engagement program on nanotechnology. Led by eleven diverse civic groups across the United States, the program events covered a wide range of applications and sparked robust discussions concerning risk and regulation. Through computer-assisted qualitative data analysis, video recordings of the events were coded for expressed levels of knowledge, positive and negative audience responses, perceptions of risk, views on regulation, and speakers' communication behaviors. These results add richness, nuance, and complexity to our perception of the public's understanding of nanotechnology, its support for regulation, and effective practices of science communication in the context of nanotechnology and other emerging technologies. Nano-Publics also offers further guidance for public engagement research, the regulation of emerging technologies, and potential science communication campaigns.